Compromiso de contratar: algunos comentarios sobre su actual regulación legislativa - Ortega Piana, Marco Antonio (2024)
The scope of the legislative regulation on the Pre-contract agreement is hereby critically commented, emphasizing that, for its contractual nature because of its mandatory purpose, the formative rules of contracts are thereto applicable, noting that due to the contents of the preliminary agreement and during its validity term which must be mandatorily predetermined, a final binding offer of what has already been fully and preliminarily agreed is formulated, which must be accepted under liability, unless there is a justifying cause. Likewise, this work highlights the legal remedies applicable in case the ordinary risk of non-performance arises, due to unjustified refusal for the timely execution of the final contract.